Crystal structure and Hirshfeld surface analysis of 2-methylquinazolin-4(3H)-one hydrochloride - Muzaffar Davlatboev; Sevara Allabergenova; Fazliddin Zulpanov; Ubaydullo Yakubov; Akmaljon Tojiboev; Tulkinjon Sattarov (Acta Crystallographica Section E: Crystallographic Communications)
The title salt (systematic name: 2-methyl-4-oxo-3,4-dihydroquinazolin-1-ium chloride), C9H9N2O+·Cl−, has orthorhombic (Pbcm) symmetry. Except for two methyl H atoms, all atoms of the molecular cation are located about a mirror plane, making the quinazolinium moiety exactly planar. Individual molecules are arranged in (001) layers in the crystal. Supramolecular features include N—H...Cl hydrogen-bonding interactions, leading to zigzag chains along [010] with D11(2) and C12(6) graph-set motifs. Additionally, weak π–π stacking interactions occur between benzene rings in adjacent layers. Hirshfeld surface analysis revealed that the most important contributions to the surface contacts are from H...H (36.1%), H...C/C...H (25.8%), and H...O/O...H (17.7%) interactions.